Problematika Dan Tantangan Santri Di Era Revolusi Industri 5.0 - Athoillah, Muhammad; Darmaningrum, Khaerunnisa Tri (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
In the current and future era of digital Society 5.0, Islamic boarding schools must also equip students with adequate technological information to support life. In this day and age, whether they like it or not, students will be exposed to the virtual world. The Era of Society 5.0 is an era where all technology cannot be separated from humans themselves. In this case, education has entered the Era of the Industrial Revolution 5.0, where the biggest era has entered the digital era. Currently, education in Islamic boarding schools is facing challenges that cannot be avoided along with the rapid development of technology. and students must be able to face how to keep up with technological developments and maintain the Islamic boarding school culture that has been tested in the Islamic boarding school journey. This research is analytical research that uses library research methods (Library Research). The research results include that changing the learning model from traditional textbooks to digital has become problematic for the world of Islamic boarding schools. This paradigm shift aims to abandon the academic and cultural traditions of Islamic boarding schools which are still preserved as Islamic boarding school identities. Islamic boarding schools must maintain their local identity (local wisdom) but must be globally competitive. There needs to be a change in the model of kiai and santri in Islamic boarding schools so that millennial students can become millennial students who can answer the challenges of the digital age.